Contemporary Appalachia : In Search of a Usable Past - Ross, Carl (Appalachian State University, 1987)
The Proceedings of the 9th Annual Appalachian Studies Conference, held in 1986 at Appalachian State University in Boone, North Carolina, offers a look at contemporary Appalachia and topics such as gender roles; native Appalachians; welfare dependency; the environment; and culture.
English
Keywords: Regional studies; Social Science; Regional Studies